Memória e resistência na migraçao para a Amazônia : O caso de Nova Londrina em Ji-Paraná, estado de Rondônia, Brasil - Felzke, Lediane Fani (Mundo Agrario.)
The occupation of Rondônia, from the 1970s, occurred in a disorganized way, since it attracted an amount of migrants which was much bigger than the settling projects could sustain. The aim of this research was to analyze the circumstances in which the district of Nova Londrina was settled, utilizing for this reason a bibliographic survey, as well as the Oral History method. The arrival in Nova Londrina, Ji-Paraná, was highlighted by conflicts between the settlers and the settling company Calama S/A. In spite of the company's violence, the colonists resisted until there was an intervention from INCRA, through a land regularization program. In this context, the Urban Center for Rural Support (NUAR) was implanted, intending to support the agricultural workers